Therapeutic efficacy of sulfadoxine-pyrimethamine, amodiaquine and the sulfadoxine-pyrimethamine-amodiaquine combination against uncomplicated Plasmodium falciparum malaria in young children in Cameroon - Basco Leonardo K.; Same-Ekobo Albert; Ngane Vincent Foumane; Ndounga Mathieu; Metoh Theresia; Ringwald Pascal; Soula Georges (The World Health Organization, 2002)
OBJECTIVE: To evaluate the therapeutic efficacy of sulfadoxine-pyrimethamine, amodiaquine, and the sulfadoxine-pyrimethamine-amodiaquine combination for the treatment of uncomplicated Plasmodium falciparum malaria in young children in Cameroon. METHODS: In a randomized study we evaluated the effectiveness and tolerance of (i) sulfadoxine-pyrimethamine (SP) (25 mg/kg body weight of sulfadoxine and 1.25 mg/kg of pyrimethamine in a single oral dose), (ii) amodiaquine (AQ) (30 mg/kg body weight in three divided daily doses), and (iii) the sulfadoxine-pyrimethamine-amodiaquine combination (SP+AQ) (same doses as in the other two treatment groups, given simultaneously on day 0) in young children in southern Cameroon. The parasitological and clinical responses were studied until day 28 in accordance with the modified 1996 WHO protocol for the evaluation of the therapeutic efficacy of antimalarial drugs. FINDINGS: Of 191 enrolled patients, 6 and 8 were excluded or lost to follow-up before day 14 and between day 14 and day 28, respectively. For the AQ-treated patients, parasitological and clinical evaluation on day 14 showed late treatment failure in 2 of 61 (3.3%) and adequate clinical response with parasitological failure in one (1.6%). There was an adequate clinical response in all patients treated with SP or SP+AQ. Therapeutic failure rates on day 28 were 13.6%, 10.2% and 0% in the SP, AQ, and SP+AQ groups, respectively. Anaemia improved in all three regimens. AQ produced faster fever clearance but was associated with more transient minor side-effects than SP. SP+AQ reduced the risk of recrudescence between day 14 and day 28 but increased the incidence of minor side-effects. CONCLUSION: SP+AQ can be recommended as a temporary means of slowing the spread of multidrug resistance in Plasmodium falciparum in Africa while the introduction of other combinations, including artemisinin derivatives, is awaited.